Building Social Distances in Neopalatial Crete: A Comparison of Accessibility in Minoan Palaces - Rapakko, Jonas (Journal of Mediterranean Archaeology, 2023)
This study compares the accessibility of the Minoan Neopalatial (ca. 1750–1490 bc) Palaces of Knossos, Phaistos, Malia, Zakros and Galatas in central and eastern Crete. The study seeks to interpret the sites’ social meaning based on analytical observations of their spatial organisation, using cost-surface analysis functions available in Geographical Information System (GIS) software. The article focuses in particular on assessing the distinct accessibility patterns provided by the different, supposedly main entrances to the sites; on the effect of ‘lengthening access’ and its social implications in the Minoan built environment; and on the gendered use of space in the hall systems of the Palaces.